Misalignment and Managed Exchange Rates : An Application to the Thai Baht - Lim, G. (IMF Working Papers; Working Paper ;, 2000)
This paper proposes a methodology for analyzing dynamic misalignment in managed exchange rate systems that combines the estimation approach to modeling the real exchange rate with the calibration approach to generating the equilibrium real exchange rate. The methodology is applied to the Thai baht and the model is estimated using only pre-July 1997 data. An analysis of the difference between the evolution of the actual real exchange rate and the generated equilibrium rate - the misalignment gap - reveals the extent to which the market was persistently factoring in an expected depreciation of the Thai baht.